THE EFFECTIVENESS OF TUMBLER USE IN REDUCING PLASTIC WASTE GENERATION AMONG STUDENTS IN DENPASAR CITY - Lucyanita Bayu Risqi; I Made Alit Widnyana; Azizah Azis; Ayuni Harianti (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2025)
This study aims to evaluate the effectiveness of using reusable water tumblers in reducing the consumption of bottled drinking water among senior high school students in Denpasar City. The research employed a mixed-methods approach, combining quantitative and qualitative methods through surveys using questionnaires and interviews with 322 respondents from two schools. The findings indicate that the average consumption of bottled drinking water before the habitual use of tumblers was 2.618 bottles per student per week, which decreased to 1 bottle per week after tumbler use became a regular practice. Pearson correlation analysis revealed a moderately strong negative relationship between tumbler usage frequency and plastic bottle consumption (r = -0.61). Furthermore, the linear regression model showed that each increase in tumbler usage level could reduce plastic bottle consumption by 0.69 bottles per week. The study concludes that the use of tumblers is effective in reducing bottled water consumption among students, although infrastructure support, such as water refill stations in schools, is still needed to optimize its impact.